WOMEN ENTREPRENEURS SERTA FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Kasus pada Pengrajin Sulaman Wanita di Jorong Lundang Kanagarian Panampuang Kab. Agam) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2013)
This study aims to identify the factors that encourage and inhibit embroidered ladies tailor in Jorong Lundang Kanagarian Panampuang to entrepreneurship, both internal factors and external factors. This study is an exploratory study that uses confirmatory factor analysis method. The population in this study is all tailor embroidery woman in Jorong Lundang Kanagarian Panampuang totaling 50 people. The data was collected using a questionnaire. The results of this study show that the internal factors that encourage respondents to entrepreneurship are personal values that are in him. External factors are factors of family support. Factors which encourage more women artisans to entrepreneurship is a factor that comes from within rather than from external factors. Meanwhile, for women artisans obstacle to entrepreneurship is a feminine factor.